Emergence of eclecticism as style: new approaches to mosque architecture in Malaysia - Zekrgoo, Amir Hossein (Tabriz Islamic Arts University, 2014)
Abstract & Introductory Remarks Eclecticism, the subject of this paper, manifests when elements from ‎different structural, spatial and decorative forms and styles, carrying features ‎representing specific and distinct cultures combine in a single work, chiefly in ‎architecture. The term ‘eclecticism’, however, in the mindset and literature of ‎societies with ancient artistic heritage, is imbued with negative denotations. This ‎is because “artistic styles” in such societies are often associated with “identity” ‎and “originality”, both of whom designate a long progress in the passage of time, ‎while eclecticism appears to lack such “valuable” process.‎ In the process of deliberating eclecticism a few questions seem ‎fundamentally relevant: How can then we define “identity” and “style” in the art ‎and architecture of younger societies? Is modern religious architecture “without ‎identity” if it does not follow the traditional trend? To what degree can architects ‎incorporate imported/alien elements in designing of local religious buildings? ‎And finally, can eclectic architecture reach the status of a proper “architectural ‎style”? ‎ Eclecticism gained rapid momentum in the field of Malaysian mosque ‎architecture during the past two decades. Significant eclectic mosques that have ‎transformed the scene and skylines of major Malaysian cities have often been ‎heavily financed by the government – an indication of conscious choice of ‎direction. The subject is yet to be studied and deserves a systematic research. ‎This paper aims to present an analytical study of the concept of ‘eclecticism’ and ‎‎‘identity’ in the context of Malaysian contemporary mosque architecture. ‎